Dental trauma involving root fracture and periodontal ligament injury: A 10-year retrospective study - Barioni, Sônia Regina Panzarini [UNESP]; Pedrini, Denise [UNESP]; Poi, Wilson Roberto [UNESP]; Sonoda, Celso Koogi [UNESP]; Brandini, Daniela Atili [UNESP]; Castro, José Carlos Monteiro de [UNESP] (FapUNIFESP (SciELO), 2008)
The purpose of this retrospective study was to analyze the cases of traumatic dental injuries involving root fracture and/or periodontal ligament injury (except avulsion) treated at the Discipline of Integrated Clinic, School of Dentistry of Araçatuba, São Paulo State University (UNESP), Brazil, from January 1992 to December 2002. Clinical and radiographic records from 161 patients with 287 traumatized teeth that had sustained root fracture and/or injuries to the periodontal ligament were examined. The results of this survey revealed that subluxation (25.09%) was the most common type of periodontal ligament injury, followed by extrusive luxation (19.86%). There was a predominance of young male patients and most of them did not present systemic alterations. Among the etiologic factors, the most frequent causes were falls and bicycle accidents. Injuries on extraoral soft tissues were mostly laceration and abrasion, while gingival and lip mucosa lacerations prevailed on intraoral soft tissues injuries. Radiographically, the most common finding was an increase of the periodontal ligament space. The most commonly performed treatment was root canal therapy. Within the limits of this study, it can be concluded that traumatic dental injuries occur more frequently in young male individuals, due to falls and bicycle accidents. Subluxation was the most common type of periodontal ligament injury. Root canal therapy was the type of treatment most commonly planned and performed.
Keywords: Comprehensive dental care; Facial injuries; Periodontal ligament; Soft tissue injuries; Tooth injuries; adolescent; adult; Brazil; endodontics; female; health survey; human; injury; male; periodontal disease; periodontal ligament; retrospective study; sex difference; tooth fracture; tooth pulp; tooth root; Adolescent; Adult; Dental Health Surveys; Dental Pulp; Female; Humans; Male; Periodontal Diseases; Periodontal Ligament; Retrospective Studies; Root Canal Therapy; Sex Factors; Tooth Fractures; Tooth Root; Young Adult